Nanogold sol plasmon discattering assay for trace carbendazim in tea coupled aptamer with Au3+-glyoxal-carbon dot nanocatalytic reaction - Bai, Hongyan; Zhang, Ran; Li, Chongning; Liang, Aihui (Frontiers in Nutrition, 2023)
A facile and new Fe-doped carbon dot (CDFe) nanosol with highly catalytic activity was prepared by hydrothermal procedure. Experiment was found that CDFe exhibited excellent catalysis for the new nano-indicator reaction of HAuCl4-glyoxal to produce gold nanoparticles (AuNPs), and the generated AuNPs have a very strong surface enhanced Raman scattering (SERS) effect at 1613 cm-1 in the presence of Victoria blue B molecular probes, and resonance Rayleigh scattering (RRS) signals at 370 nm. The aptamer (Apt) suppressed the catalysis of CDFe to cause the SERS and RRS signals decreasing. With the addition of CBZ, the specific Apt reaction occurred to restore the catalysis of CDFe, and resulting in a linear increase in the signals of RRS and SERS. Based on this, this new nanocatalytic amplification indicator reaction was coupled with a specific Apt reaction of carbendazim (CBZ), to construct a new CDFe catalytic amplification-aptamer SERS/RRS discattering assay for ultratrace CBZ, which was used to analyze CBZ in tea samples with satisfactory results. In addition, this biosensoring platform can be also used to assay profenofos.